Perancangan Site Plan dan Pendampingan Digital BUMDes di Desa Klampitan, Kecamatan Purwoasri, Kabupaten Kediri untuk Akselerasi Desa Wisata 2026 - Ahmada Rana Rafidhah; Muhammad Ivan Surya Akbar; Weka Nurkharisma; Amanda Puspita; Sifaul Ummah; Tahta Dhilli Arsika; Muhammad Faqih Mutafannin; Nurul Khoirotin; Diah Handayani (Jurnal Pengabdian Nasional (JPN) Indonesia, 2026)
Tourism village development through Village-Owned Enterprises (BUMDes) serves as a key strategy for rural economic empowerment. Klampitan Village, Purwoasri District, Kediri Regency, encounters several obstacles including limited human resource capacity, weak digital promotion, and lack of systematic spatial planning for BUMDes development. The community service program aimed to design a BUMDes site plan as a guideline for physical tourism area development and to enhance digital promotion capacity. A qualitative participatory approach was employed through the Asset-Based Community Development (ABCD) framework for village asset mapping, complemented by SWOT analysis for strategy formulation. Implementation took place from July to August 2025, involving 10 key informants through observation, interviews, and Focus Group Discussions (FGDs). Data validation was conducted using source triangulation and member checking. The program produced a conceptual BUMDes site plan comprising 11 main sections with economic, social, educational, and recreational functions. Additionally, official BUMDes social media accounts were established as digital promotion channels. Evaluation showed 92% community participation and improved capabilities of MSME actors in utilizing social media for product marketing. These achievements demonstrate that the program not only generated initial plans and facilitation but also established institutional foundations and human resource capacity for sustainable BUMDes management. The resulting site plan and digital enhancement function as initial instruments supporting the acceleration of Klampitan Village toward becoming a tourism village in 2026.